Fibrocystic Disease And Duct Ectasia Of The Breast; Similarities And Differences - Salih , Zainab Mohammed (Journal of Neonatal Surgery, 2025)
Introduction: The breast is a dynamic organ that undergoes many physiological changes during the female’s life. Fibrocystic breast disease is characterized by a group of proliferative cell elements while in mammary duct ectasia there is abnormal dilatation of the mammary ducts. Patients and methods: This retrospective study included 116 female patients divided into two groups, the first group were patients with fibrocystic disease and the second having duct ectasia. Both groups were compared for clinical differences and similarities. Result: The mean age patients was 33.63 years with a mean BMI of 27.99 with no significant differences between both groups regarding both parameters (P values 0.09 & 0.238). Caffeine, alcohol consumption, smoking, and family history of breast cancer also showed no significant correlation (P values 0.618, 1.00, 0.438, and 1.00). Pain was present in 81% of fibrocystic disease and 75.9% of duct ectasia patients. The pain was non-cyclical in most patients of both groups, cyclical pain was commoner in fibrocystic disease than duct ectasia (34.5% vs. 27.6%). All the correlations with pain were not significant regarding the presence or absence of pain, its location regarding breast quadrants, and whether cyclical or not (P values 0.652, 0.535, and 0.547) respectively. Breast tenderness was commoner in fibrocystic disease (77.6%) compared to duct ectasia (65.5%) but the correlation was not significant (P value 0.217). Nipple discharge and retraction was present in 44% and 10.6% of patient with duct ectasia respectively and were absent in patient with fibrocystic disease with a very significant between both groups both clinical findings (P values 0.000 and 0.027) respectively. Breast nodularity was detected in 5.2% of duct ectasia patients and 27.6% of fibrocystic disease patients. Breast lump was more predominant in fibrocystic disease compared to duct ectasia patients (22.4% vs.1.7%) with a very significant difference between both groups (P values 0.002 & 0.001) respectively. Conclusion: Benign breast disorders are common in females, fibrocystic disease and duct ectasia are among the commonest ones. Breast pain and tenderness are common in both diseases, nipple discharge and retraction are more predominant features of duct ectasia while nodularity and lump are more predominant in fibrocystic disease.